The GMRT High Resolution Southern Sky Survey for Pulsars and Transients. VI. Discovery of Nulling, Localization, and Timing of PSR J1244–4708 - S. Singh; J. Roy; Shyam S. Sharma; B. Bhattacharyya; S. Kudale (The Astrophysical Journal, 2023)
Many pulsars in the known population exhibit nulling, which is characterized by a sudden cessation and subsequent restoration of radio emission. In this work, we present the localization, timing, and emission properties of a pulsar discovered by the GMRT High Resolution Southern Sky survey: J1244–4708. Moreover, we find that this pulsar shows nulling, with a nulling fraction close to 60%. A quasiperiodicity is also seen in the nulling from this pulsar with two timescales. We demonstrate the broadband nature of nulling in this pulsar using simultaneous observations in band-3 (300–500 MHz) and band-4 (550–750 MHz) with the upgraded GMRT. We also present a comparison of the efficiency of various search approaches such as single pulse search, fast folding algorithm (FFA)–based search, and fast Fourier transform–based search to search for nulling pulsars. We demonstrated that the FFA search is advantageous for detecting extreme nulling pulsars, which is also confirmed with multiple epochs of observations for the nulling pulsars using the GMRT.